Glucose Transporters in Diabetic Kidney Disease—Friends or Foes? - Wasik, Anita A.; Lehtonen, Sanna (Frontiers in Endocrinology, 2018)
Diabetic kidney disease (DKD) is a major microvascular complication of diabetes and a common cause of end-stage renal disease worldwide. DKD manifests as an increased urinary protein excretion (albuminuria). Multiple studies have shown that insulin resistance correlates with the development of albuminuria in non-diabetic and diabetic patients. There is also accumulating evidence that glomerular epithelial cells or podocytes are insulin sensitive and that insulin signaling in podocytes is essential for maintaining normal kidney function. At the cellular level, the mechanisms leading to the development of insulin resistance include mutations in the insulin receptor gene, impairments in the phosphoinositide 3-kinase (PI3K)/AKT signaling pathway or perturbations in the trafficking of glucose transporters (GLUTs), which mediate the uptake of glucose into cells. Podocytes express several GLUTs, including GLUT1, GLUT2, GLUT3, GLUT4 and GLUT8. Of these, the most studied ones are GLUT1 and GLUT4, both shown to be insulin responsive in podocytes. In the basal state, GLUT4 is preferentially located in perinuclear and cytosolic vesicular structures and to a lesser extent at the plasma membrane. After insulin stimulation, GLUT4 is sorted into GLUT4 containing vesicles (GCVs) that translocate to the plasma membrane. GCV trafficking consists of several steps, including approaching of the GCVs to the plasma membrane, tethering and docking, after which the lipid bilayers of the GCVs and the plasma membrane fuse, delivering GLUT4 to the cell surface for glucose uptake into the cell. Studies have revealed novel molecular regulators of the glucose transporter trafficking in podocytes and unraveled unexpected roles for GLUT1 and GLUT4 in the development of DKD, summarized in this review. These findings pave the way for better understanding of the mechanistic pathways associated with the development and progression of DKD and aid in the development of new treatments for this devastating disease.